Conservation and diversity in the secondary forward photodynamics of red/green cyanobacteriochromes. Issue 10 (17th September 2019) - Jenkins, Adam J.; Gottlieb, Sean M.; Chang, Che-Wei; Hayer, Randeep J.; Martin, Shelley S.; Lagarias, J. Clark; Larsen, Delmar S.
Abstract : The forward secondary dynamics of eight cyanobacteriochrome domains were characterized, revealing that half of them incorporate an unproductive 15 Z Po subpopulation and that a nearly conserved mechanism of blue-shifting intermediates is revealed. Abstract : Cyanobacteriochromes (CBCRs) are photosensitive proteins that are distantly related to the phytochrome family of photoreceptors and, like phytochromes, exhibit photoactivity initiated by the excited-state photoisomerization of a covalently bound bilin chromophore. The canonical red/green photoswitching sub-family is the most studied class of CBCRs studied to date. Recently, a comparative study of the ultrafast (100 fs–10 ns) forward photodynamics of nine red/green photoswitching CBCR domains isolated from Nostoc punctiforme were reported (S. M. Gottlieb, P. W. Kim, C.-W. Chang, S. J. Hanke, R. J. Hayer, N. C. Rockwell, S. S. Martin, J. C. Lagarias and D. S. Larsen, Conservation and Diversity in the Primary Forward Photodynamics of Red/Green Cyanobacteriochromes, Biochemistry, 2015, 54, 1028–1042). We extend this study by characterizing the secondary (10 ns–1 ms) forward photodynamics of eight red/green photoswitching CBCRs from N. punctiforme with broadband time-resolved absorption spectroscopy. We demonstrate that the dynamics of these representative red/green CBCRs can be separated into two coexisting pathways involving a photoactive pathway that is successful in generating the terminal light-adapted 15 E Pg population and an unsuccessful pathway that stalls after generating a meta-stable Lumi-Of intermediate. The photoactive pathway evolves through a similar mechanism from excitation of the dark-adapted 15 Z Pr state to generate a far-red absorbing Lumi-Rf and then via a succession of blue-shifting photointermediates to ultimately generate the 15 E Pg state. This suggests a steady deviation from planarity of the bilin chromophore during the dynamics. While, the general mechanism for this evolution is conserved among these CBCBs, the timescales of these dynamics deviate significantly. Only half of the characterized CBCRs exhibit the unproductive pathways due to photoexcitation of dark-adapted 15 Z Po sub-population that upon photoexcitation generates a meta-stable Lumi-Of intermediate, which eventually decays back to the 15 Z Po subpopulation. 15 Z Po is ascribed the horizontal Asp657 configuration that disrupts H-bonding with the chromophore in the dark-adapted state; its presence can be identified via enhanced absorption of high-energy tail of the electronic absorption spectrum.